Pengaruh Tax Minimization dan Audit Tenure Terhadap Transfer Pricing - Luthfi Setyo Maharani; Dirvi Surya Abbas; Triana Zuhrotun Aulia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research was conducted to determine the effect of tax minimization and audit tenure on transfer pricing with firm size as a moderating variable carried out on manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample used in this research was selected using a purposive sampling method based on several predetermined criteria and resulted in 23 company samples with 115 observation data. The data analysis method uses panel data regression analysis which is tested using Eviews 12 software. The hypothesis testing method uses a significance level of 5%. The research results show that only the audit tenure variable is proven to have a negative influence on the company's decision to carry out transfer pricing practices, while the tax minimization variable has no effect on the company's decision to carry out transfer pricing practices.